Statistical Analysis as the Basis for the Practice of Modernizing Personnel Management: International Experience - Aleksandrovich Endovitsky, Dmitry; Borisovna Durakova, Irina; ., . (International Journal of Engineering and Technology, 2018)
The article is devoted to the issues of modernization of personnel management from the standpoint of the results of the statistical analysis of its framework conditions, studied as social and mass phenomena. Terms of implementation of work with the staff received extensive coverage in the scientific literature, profile-oriented to management, economics, sociology, psychology and law. Insufficient research base for statistical conclusions on the scale of phenomena, their groupings, and dynamics makes it difficult to work on timely diagnosis of the real model of personnel management and the formation of a vector of its modernization. The article systematizes the concept of the components of the two-contour framework, which defines the playing space of work with personnel, shows the classifications of the working age, family models, systematizes the scientific concepts of generations and the dynamics of value systems. Grounds for modernizing the practice of personnel management in organizations are justified. The methods of statistical analysis are given: observation, groupings, and classifications. Â Â Â